Quality Assurance for Iraqi Bottled Water Specifications - May George Kassir; Lamyaa Mohammed Dawood; Fatin Fuad (Journal of Engineering, 2015)
In this research the specifications of Iraqi drinking bottled water brands are investigated throughout the comparison between local brands, Saudi Arabia and the World Health Organization (WHO) for bottled water standard specifications. These specifications were also compared to that of Iraqi Tap Water standards. To reveal variations in the specifications for Iraqi bottled water, and above mentioned standards some quality control tools are conducted for more than 33% of different bottled water brands (of different origins such as spring, purified,..etc) in Iraq by investigating the selected quality parameters registered on their marketing labels. Results employing Minitab software (ver. 16) to generate X bar, and Pareto chart. It was found from X bar charts that the quality parameters of some drinking bottled water brands are not within Iraqi standards set by the “Central Agency for Standardization and Quality Control” such as pH values, Fe, Na, and Mg concentrations. While the comparison of previously mentioned standard specifications through radar chart many important issues are detected such as the absence of lower limits the whole bottled water quality parameters such as for Na and Mg also the radar chart shows that Iraqi bottled and tap water specifications are almost equal in their quality values. Also the same chart pictured the limited range of Iraqi specifications compared to that of Saudi Arabia, and WHO and the need to introduce other water specifications such as K, Na, etc. This confirms the need to improve Iraqi bottled water specifications since it was introduced on 2000. These results also highlighted the weakness of quality assurance activities since only 33 % of the investigated companies registered the whole water quality specifications as shown in Pareto chart. Other companies do not register any quality characteristics. Also certain companies should be stopped due to non-conforming specifications, yet these companies are still producing and selling their products in the local market. Quality assurance requires continually monitor the reliability (accuracy and precision processes) of Iraqi drinking bottled water companies to match the Iraqi Specification Standards, and those companies should continually approve “How good (accurate and precise) is their product( water quality) produced?”.